(untitled) (Bangladesh Journal of Child Health, 2017)
Cystic fibrosis (CF) is said to be the most common lethal inherited disease of the white population. It affects the exocrine glands of body, primarily of the gastrointestinal and respiratory system. CF is caused by one of a large numbers of mutations of the gene for a protein called the cystic fibrosis transmembrane conductance regulator (CFTR). This CFTR regulates chloride and sodium transport across epithelial membranes. The main complications involve in the lungs, with damage to the small and large airways by chronic and recurrent bacterial infections. Other major consequences include pancreatic malfunction, leading to malabsorption of nutrients and vitamins with consequent impaired growth and development and in older patient diabetes. Diagnosis is usually done by sweat test or identification of two CF-causing mutations in patients with characteristics symptoms. Treatment is supportive through aggressive multidisciplinary care. The prognosis of CF has improved due to earlier diagnosis through screening, better treatment and access to health care. Although CF is a rare disease in Bangladesh, but its possibility should be kept in mind in appropriate circumstances. Bangladesh J Child Health 2016; VOL 40 (3) :174-178